The influence of teacher beliefs, opportunity to learn, and propensity factors on creative mathematics teaching - Ramasamy, Kumaravalu (Kulliyyah of Education, International Islamic University Malaysia, 2020)
The emphasis on nurturing students' mathematical creativity in schools is not new in Malaysian educational landscape. More than ever before mathematics teachers are now expected to foster creativity among students through creative teaching. However, not all mathematics teachers embrace creative teaching and many reject it especially at the secondary level mathematics. The present study was designed to investigate the effect of three teacher related factors namely beliefs, opportunity to learn and propensity on creative teaching in mathematics based on socio-cultural theories of teacher learning especially Goos' Teachers as Learners framework. The main purpose of the study was to evaluate the causal relationships between teachers as learners factors ( mathematics teachers' beliefs, opportunity to learn, propensity factors) and creative mathematics teaching from one hypothesized to two alternative structural models. The study also examined the invariance of the structural model across samples of lower secondary (n=157) and upper secondary (n=197) mathematics teachers. The study involved 354 random samples of secondary mathematics teachers chosen by using stratified sampling from all eight districts of Selangor state. The instrument for the cross-sectional survey was adapted mainly from Palaniappan (2009) for creative teaching factor, Stipek (2001) for beliefs factor, Desimone (2009) for opportunity to learn and Kunter et al (2011) for propensity. The study hypothesized that creative teaching is directly or indirectly influenced by beliefs, teacher opportunity to learn and teacher propensity factors. Three alternative models were tested to examine which fit the data well. The hypothesis was supported by The Alternative Model II of which opportunity to learn was the only direct predictor of creative mathematics teaching. Teachers' beliefs indirectly influenced creative teaching via propensity factors. The findings revealed that opportunity to learn and propensity factors were positively correlated. The invariance analysis of the structural model across lower secondary samples and upper secondary samples revealed that the structural model was similar across both groups. The findings suggest for quality learning opportunity for teachers in order to foster creativity in classrooms